Genetic Loss of IK1 Causes Adrenergic-Induced Phase 3 Early Afterdepolariz ations and Polymorphic and Bidirectional Ventricular Tachycardia. (September 2020) - Reilly, Louise; Alvarado, Francisco J.; Lang, Di; Abozeid, Sara; Van Ert, Hannah; Spellman, Cordell; Warden, Jarrett; Makielski, Jonathan C.; Glukhov, Alexey V.; Eckhardt, Lee L.
Abstract : Background: Arrhythmia syndromes associated with KCNJ2 mutations have been described clinically; however, little is known of the underlying arrhythmia mechanism. We create the first patient inspired KCNJ2 transgenic mouse and study effects of this mutation on cardiac function, I K1, and Ca 2+ handling, to determine the underlying cellular arrhythmic pathogenesis. Methods: A cardiac-specific KCNJ2 -R67Q mouse was generated and bred for heterozygosity (R67Q +/− ). Echocardiography was performed at rest, under anesthesia. In vivo ECG recording and whole heart optical mapping of intact hearts was performed before and after adrenergic stimulation in wild-type (WT) littermate controls and R67Q +/− mice. I K1 measurements, action potential characterization, and intracellular Ca 2+ imaging from isolated ventricular myocytes at baseline and after adrenergic stimulation were performed in WT and R67Q +/− mice. Results: R67Q +/− mice (n=17) showed normal cardiac function, structure, and baseline electrical activity compared with WT (n=10). Following epinephrine and caffeine, only the R67Q +/− mice had bidirectional ventricular tachycardia, ventricular tachycardia, frequent ventricular ectopy, and/or bigeminy and optical mapping demonstrated high prevalence of spontaneous and sustained ventricular arrhythmia. Both R67Q +/− (n=8) and WT myocytes (n=9) demonstrated typical n-shaped I K1 IV relationship; however, following isoproterenol, max outward I K1 increased by ≈20% in WT but decreased by ≈24% in R67Q +/− ( P <0.01). R67Q +/− myocytes (n=5) demonstrated prolonged action potential duration at 90% repolarization and after 10 nmol/L isoproterenol compared with WT (n=7; P <0.05). Ca 2+ transient amplitude, 50% decay rate, and sarcoplasmic reticulum Ca 2+ content were not different between WT (n=18) and R67Q +/− (n=16) myocytes. R67Q +/− myocytes (n=10) under adrenergic stimulation showed frequent spontaneous development of early afterdepolarizations that occurred at phase 3 of action potential repolarization. Conclusions: KCNJ2 mutation R67Q +/− causes adrenergic-dependent loss of I K1 during terminal repolarization and vulnerability to phase 3 early afterdepolarizations. This model clarifies a heretofore unknown arrhythmia mechanism and extends our understanding of treatment implications for patients with KCNJ2 mutation. Abstract : Supplemental Digital Content is available in the text.